Optical properties of zinc lead tellurite glasses - Alazoumi, Salah Hassan; Abdul Aziz, Sidek; El-Mallawany, Raouf Ahmed H.; Aliyu, Umar Sa'ad; Mohamed Kamari, Halimah; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Ushah, Abdulbaset (Elsevier, 2018)
Tellurite glass systems in the form of [ZnO]x [(TeO2)0.7-(PbO)0.3]1-x with x = 0.15, 0.17, 0.20, 0.22 and 0.25 mol% were prepared using the melt quenching technique. XRD of the prepared samples have been measured for all samples. Both FTIR (280–4000 cm−1) and UV-Vis (200–800 nm) spectra have been measured. Optical band gap and refractive index were calculated for every glass sample. Density of glass, molar volume and oxygen packing density (OPD) were obtained. Values of the direct, indirect band gap ranged were found in the range 3.41–3.94 eV and 2.40–2.63 eV with increasing of ZnO concentration. Refractive index 2.58 and dielectric constant 6.66 were heigh at 17 ZnO mol% concentration. Molar polarizability, metallization criterion, polaron radius have been calculated for every glass composition.